Cascade catalysis – strategies and challenges en route to preparative synthetic biology. Issue 27 (5th February 2015) - Muschiol, Jan; Peters, Christin; Oberleitner, Nikolin; Mihovilovic, Marko D.; Bornscheuer, Uwe T.; Rudroff, Florian
Abstract : In this feature article recent progress and future perspectives of cascade catalysis combining bio/bio or bio/chemo catalysts are presented. Abstract : Nature's smartness and efficient assembling cascade type reactions inspired biologists and chemists all around the world. Tremendous effort has been directed towards the understanding and mimicking of such networks. In recent years considerable progress has been made in developing multistep one-pot reactions combining either advantage of chemo-, regio-, and stereoselectivity of biocatalysts or promiscuity and productivity of chemocatalysts. In this context several concepts, inspired by different disciplines (biocatalysis, metabolic engineering, synthetic chemistry, and material science), have been evolved. This review will focus on major contributions in the field of cascade reactions over the last three years.